Hidden under data: Evolution of academic social networks - Ortega-Priego, José-Luis (Anuario ThinkEPI, 2018)
The evolution of the top academic social networks: Mendeley, Academia.edu, and ResearchGate is analyzed. This study tests the current health of these platforms and determines which growth stage they are in by tracking the annual number of new members and documents. In addition, the degree of transparency of these sites is discussed in relation to publicly available information about their services. The results show these platforms are reaching a change in cycle, where the increase rates are slowing down, decreasing the aggregation rate of documents and users.